INTERPRETATION OF THE VERSES OF THE QUR'AN REGARDING HUMAN RESOURCE MANAGEMENT - Mahanum, Mahanum; Syahputra, Ahmad Risqi (Universitas Dharmawangsa, 2020)
This paper reveals that human resources are the greatest power in the processing of all the resources that exist on earth. Humans were created by Allah Almighty. as a caliph on earth to manage the earth and the resources in it for the welfare of mankind itself, creatures and the entire universe, because basically all of Go's creations that exist on earth were deliberately created by Allah for the benefit of mankind. Therefore, these existing resources must be managed properly because they are a mandate carried by humans who will be held accountable in the afterlife. To get good management, humans are required to master science. In surah ar-Rahman verse 33, Allah has advised humans to study as widely as possible without limits in order to prove the Almighty of Allah. And the knowledge in question must be directed to the study of the Koran and Hadith. Humans have the potential to be the noblest of creatures and also the potential to be the lowest of creatures